(3OjhGf GdhChGA GdOeTbjs - (3eMeO Hf CMeO GdZSGfj GdOeTbj, CHh GdaQL, GdeYQha H` GdhChGA,J (B385 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3hegaga cGdZUf gRJg GdUHG aUHG Edjg ef GdbdhH ghGA s
(3BNQgG (B:s
(3YGOfj ef CYGO QhMj EdjG HYO Cf SdW GdMeGe YdjG Cj ejJ eKdj hdSJ JQGg YGOg Cdag aCUHM MjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQgG eY OjhGf GdCHdg GdHZOGOjs
(3fSNI KGfjIs
(3hGdOjhGf oeQJH Ydi MQha GdoeYLes
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs